(untitled) (Scientific journal of the Fergana State University, 2025)
In the article, the issue of women, their participation in socio-political relations, the fact that their rights and freedoms are ensured in practice is an important index of the development of states and democracy. Also, attention to women has risen to the level of real state policy: its legal and institutional foundations have been fundamentally improved. This led to the emergence of ideas that women also have a position as a productive force.